Life-history writing and the anthropological silhouette - Zeitlyn, D; Zeitlyn, D (John Wiley and Sons, 2008)
In this paper I explore ways in which anthropologists can and have approached life-histories. I consider some of the theoretical background to this and discuss life-writing, biography and autobiography. In conclusion, I see the life-history as grounding anthropological analysis. As a model for future work I introduce the idea of an 'anthropological silhouette': less complete than a biography, and partial, but demonstrably based on an individual, and honest about its limitations and incompleteness. © 2008 European Association of Social Anthropologists (EASA).